2018
DOI: 10.1371/journal.ppat.1007052
|View full text |Cite
|
Sign up to set email alerts
|

RitR is an archetype for a novel family of redox sensors in the streptococci that has evolved from two-component response regulators and is required for pneumococcal colonization

Abstract: To survive diverse host environments, the human pathogen Streptococcus pneumoniae must prevent its self-produced, extremely high levels of peroxide from reacting with intracellular iron. However, the regulatory mechanism(s) by which the pneumococcus accomplishes this balance remains largely enigmatic, as this pathogen and other related streptococci lack all known redox-sensing transcription factors. Here we describe a two-component-derived response regulator, RitR, as the archetype for a novel family of redox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…Expression and purification of PA0709 and PA3390 were carried out as described in reference 147 . His 6 -tagged PA0709 and PA3390 proteins were expressed in E. coli T7 Express lysY i/q cells (New England BioLabs Inc., Ipswich, MA) carrying pET15DG1-PA0709 or pET15DG1-PA3390.…”
Section: Methodsmentioning
confidence: 99%
“…Expression and purification of PA0709 and PA3390 were carried out as described in reference 147 . His 6 -tagged PA0709 and PA3390 proteins were expressed in E. coli T7 Express lysY i/q cells (New England BioLabs Inc., Ipswich, MA) carrying pET15DG1-PA0709 or pET15DG1-PA3390.…”
Section: Methodsmentioning
confidence: 99%
“…Female, 8–10 week old MF1 mice weighing ~30–35 g (Charles River, UK), were anesthetized with 2.5% v/v isoflurane (Astra Zeneca, Macclesfield, UK) over oxygen (2–2.5 liter/min). For the pneumonia model, ~1.5 × 10 6 pneumococci, in 50 μL PBS (Gaspar et al, 2014; Glanville et al, 2018) were administered dropwise into the nostrils of the anesthetized mouse, held vertically. After infections, CFU were determined to ensure that the intended number of pneumococci had been administered.…”
Section: Methodsmentioning
confidence: 99%
“…TCS02 (WalR/K), the only TCS essential for pneumococcal viability, is associated with cell wall peptidoglycan metabolism [28,29]; TCS03 (LiaR/S) senses cell wall damage and inhibits autolysis [30], TCS04 (PnpR/S) regulates uptake of inorganic phosphate [31,32]; TCS06 (CbpR/S) activates expression of choline-binding protein A or PspC [33,34]; TCS08 is involved in the cellobiose uptake [35], production of pilus-1 [16] and surface protein PavB [16]; TCS13 (BlpR/H) regulates the production of bacteriocins (pneumocins) [36][37][38]. The orphan response regulator RR14 represses the transcription of the pneumococcal iron uptake (Piu) and other nutrient uptake loci in response to oxidative stress [39,40]. The cellular functions of the remaining five TCSs (1, 7, 9, 10 and 11) are poorly characterized.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…RR14 represses the transcription of the pneumococcal iron uptake (Piu) and nutrient uptake loci [39]. A recent study has shown that RR14 serves as a principal regulator in response to oxidative stress via the cysteine-mediated dimerization, which enhances pneumococcal tolerance to hydrogen peroxide and other oxidants [40]. S. pneumoniae is famous for its production of millimolar range of hydrogen peroxide as a metabolic byproduct of pyruvate oxidase SpxB [67,68].…”
Section: Plos Pathogensmentioning
confidence: 99%